Meta-analysis of clinical efficacy of thoracoscopy and robotic surgery in the treatment of mediastinal tumors - Jiying Dang; Shize Sun; Zhengqi Wu; Yidong Shan; Huiling Zhang (World Journal of Surgical Oncology, 2024)
Abstract Objective Comparing the clinical efficacy of thoracoscopy and robotic surgery in the treatment of mediastinal tumors using meta-analysis. Methods Computer retrieval of PubMed, Embase, The Cochrane Library, and Web of Science databases for literature comparing the clinical effects of video-assisted thoracic surgery (VATS) and robot-assisted thoracic surgery (RATS) in treating mediastinal tumors, with the retrieval time limit from the establishment of the database to September 2023. Two evaluators independently screened the literature, extracted data, and assessed the risk of bias. Meta-analysis was performed using RevMan 5.4. Results A total of 19 articles were included, with a total of 3517 patients. The results of the Meta-analysis showed that the RATS group had less intraoperative bleeding [MD =  − 5.20, 95%CI (− 9.28, − 1.12), P = 0.01], lower rate of conversion to thoracotomy [OR = 0.41, 95%CI (0.23, 0.72), P = 0.002], lower rate of total postoperative complications [OR = 0.57, 95%CI (0.34, 0.95), P = 0.03], shorter postoperative drainage time [MD =  − 0.72, 95%CI (− 1.13, − 0.32), P = 0.0004], and shorter postoperative hospital stay [MD =  − 0.90, 95%CI (− 1.16, − 0.65), P < 0.001], in comparison with the VATS group. There was an insignificant difference between the two groups in terms of tumor size [MD =  − 0.02, 95%CI (− 0.33, 0.30), P = 0.91] and operation time [MD = 0.17, 95%CI (− 7.61, 7.94), P = 0.97]. However, in regards to hospitalization costs [MD = 2634.75, 95%CI (991.62, 4277.88), P = 0.002], the RATS group was more expensive than the VATS group. Conclusion Robot-assisted mediastinal tumor resection surgery has more advantages in terms of intraoperative bleeding, conversion to thoracotomy rate, total postoperative complication rate, postoperative drainage time, and postoperative hospital stay, in comparison with thoracoscopic-assisted mediastinal tumor resection surgery. There is an insignificant difference in tumor size and operation time between the two surgeries. However, robot-assisted mediastinal tumor resection surgery increases hospitalization costs.